New Data from Minor Mountainous Lakes as High-Resolution Geological Archives of the Northern Apennines, Italy: Lake Moo - Yago Nestola; Stefano Segadelli (Geosciences, 2025)
Sedimentary basins developed in mountain belts are natural traps of catchment erosion products and can produce comprehensive palaeoflood records that extend beyond instrumental or historical data. This study investigates the Lake Moo plain (1120 m a.s.l.), located in the Mt. Ragola (1712 m a.s.l.) ophiolitic massif in the Northern Apennines (Italy), which serves as an excellent case study for inferring the chronology of past flood events due to its position relative to the dominant atmospheric flow and its favorable geological and geomorphological characteristics. The Northern Apennines is a relatively understudied region regarding the reconstruction of past Holocene flood activity through the analysis of lake sediments and peat bogs, compared with areas like the Alps. The main objective of this research was to analyze sediment cores taken from a lake situated in a catchment area dominated by ultramafic rock lithologies and associated residual weathering cover deposits. This allowed us to detect and characterize past flood events in the Ligurian–Emilian Apennines. A multidisciplinary approach, integrated with reference data on geology, geomorphology, pedology, and petrography, enabled a more detailed description of the changes in the hydrologic cycle. Collectively, these data suggest that periods of increased past flood activity were closely linked to phases of rapid climate change at the scale of the Ligurian–Emilian Apennines. The preliminary results suggest that floods occurring during periods of temperature drops have distinct characteristics compared with those during temperature rises.